2017
DOI: 10.1016/j.cell.2017.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Mating in the Closest Living Relatives of Animals Is Induced by a Bacterial Chondroitinase

Abstract: Summary We serendipitously discovered that the marine bacterium Vibrio fischeri induces sexual reproduction in one of the closest living relatives of animals, the choanoflagellate Salpingoeca rosetta. Although bacteria influence everything from nutrition and metabolism to cell biology and development in eukaryotes, bacterial regulation of eukaryotic mating was unexpected. Here we show that a single V. fischeri protein, the previously uncharacterized EroS, fully recapitulates the aphrodisiac-like activity of li… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
125
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 110 publications
(129 citation statements)
references
References 61 publications
(87 reference statements)
2
125
1
1
Order By: Relevance
“…Only under starvation conditions would a small fraction of the S. rosetta population mate [21]. A serendipitous observation revealed that specific environmental bacteria, missing from most laboratory cultures, were capable of triggering a population-wide switch to sexual reproduction [22 •• ]. …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Only under starvation conditions would a small fraction of the S. rosetta population mate [21]. A serendipitous observation revealed that specific environmental bacteria, missing from most laboratory cultures, were capable of triggering a population-wide switch to sexual reproduction [22 •• ]. …”
Section: Introductionmentioning
confidence: 99%
“…Genetic experiments confirmed that the diploid products of cell and nuclear fusion later generated meiotic progeny, demonstrating that V. fischeri bacteria induce the full sexual cycle in S. rosetta (Figure 1b). We subsequently found that Vibrio orientalis and Vibrio tubiashii elicit swarming and mating in S. rosetta , while other species tested did not, suggesting that S. rosetta mating in nature might be regulated by some, but not all species of Vibrio bacteria [22 •• ]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…An additional example from S. rosetta suggests that bacteria regulate eukaryotic sexual reproduction. Vibrio fischeri secretes chondroitin lyase, which in S. rosetta initiates the switch from asexual to sexual reproduction by inducing swarming [61]. …”
Section: The Importance Of Nonmodel Organisms In Metaorganism Researchmentioning
confidence: 99%
“…[11] While this organism is known to form its namesake rosette colonies by (asexual) cell division, the authors clearly noticed different cells swarming together. Upon closer inspection, the authors also observed that within this clump, the organisms began to pair off and reproduce sexually (Figure 2), observing nuclear combination to form a diploid parent.…”
mentioning
confidence: 99%